+0  
 
0
416
8
avatar

Let $b$ and $c$ be constants such that the quadratic $-2x^2 +bx +c$ has roots $3+\sqrt{5}$ and $3-\sqrt{5}$. Find the vertex of the graph of the equation $y=-2x^2 + bx + c$.

Guest Feb 19, 2018
 #1
avatar+12725 
+2

There MIGHT (probably) be an easier way, but here is ONE way:

 

(x+(-3-sqrt5))(x+(-3+sqrt5))   is given in the question for the roots

   if you multiply these two term out you will get

x^2-6x+4    now multiply by -2

 

-2x^2 +12x-8 =0     (a parabola)

 

to find vertex take derivative and set equal to zero

-4x+12 = 0     x = 3    substitue this into the equation

        to get      y=10     for the vertex    3,10

ElectricPavlov  Feb 19, 2018
edited by ElectricPavlov  Feb 19, 2018
 #3
avatar
0

Should it be (x+(3-sqrt 5))(x+(3+sqrt5))?

Guest Feb 21, 2018
 #4
avatar
0

Shouldnt it be (-3,10)?

Guest Feb 21, 2018
 #5
avatar+12725 
+2

The roots are given   as   3+-sqrt5

so one part would be

 

x+(- 3+sqrt5) =0  

x-3+sqrt5  = 0     solve for x   (add  (3 and subtract sqrt5) from both sides )

x= 3 -sqrt5

 

 

   and the other would be  x+( -3-sqrt5)  =0

            x-3-sqrt5    solve for x  (add 3 and sqrt 5 to both sides  

                                          x = 3+sqrt5

 

These are the roots given in the question....

ElectricPavlov  Feb 21, 2018
 #6
avatar+12725 
+2

Here is a graph  

ElectricPavlov  Feb 21, 2018
 #7
avatar+12725 
+2

y=  a (x-h)^2  +k        and

y= -2 (x-3)^2 +10

 

Now can you see that a =-2    h=3   k = 10  ???

ElectricPavlov  Feb 21, 2018
 #2
avatar+12725 
+2

OK.....another way...

AFTER you get to

-2x^2 +12x -8                arrange into vertex form  y=a(x-h)^2 +k    the vertex is h,k

-2{ x^2 -6x +4}

-2{(x-3)^2 +4 -9}

-2 {(x-3)^2 -5}

-2 (x-3)^2 +10             so  h,k is the vertex   =   3,10

ElectricPavlov  Feb 19, 2018
 #8
avatar+93305 
+1

I am quite sure EP will be correct but I will take a look:

 

Let b and c be constants such that the quadratic \(-2x^2 +bx +c\)   

has roots \(3+\sqrt{5}\)  and \(3-\sqrt{5}\).

Find the vertex of the graph of the equation   

\(y=-2x^2 + bx + c\)

 

The roots of a quadratic   \( ax^2+bx+c\)  is the answers to   \( ax^2+bx+c=0\)

And the answers to this are given by the quadratic equation

 

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\\ x=\frac{-b}{2a}\pm\frac{\sqrt{b^2-4ac}}{2a}=3\pm\sqrt5 \)

 

This means that  \(x=\frac{-b}{2a}\) = 3      must be exactly halfway between the two roots.!!

 

So the axis of symmetry is x=3 and the vertex lies on this line so the x value of the vertex is 3

The y value will be    \(y=-2*3^2+bx+c = -18+3b+c \)

 

This is fine but you need to find the vleu of b and c       frown

 

From the equation above I can see that 

\(\frac{-b}{2a}=3 \qquad and \qquad \pm\frac{\sqrt{b^2-4ac}}{2a}=\pm\sqrt5\\ a=-2\qquad so\\ \frac{-b}{-4}=3 \qquad and \qquad \pm\frac{\sqrt{b^2+8c}}{-4}=\pm\sqrt5\\ b=12 \qquad and \qquad \pm\frac{\sqrt{b^2+8c}}{4}=\pm\sqrt5\\ b=12 \qquad and \qquad \frac{b^2+8c}{16}=5\\ b=12 \qquad and \qquad b^2+8c=80\\ b=12 \qquad and \qquad 144+8c=80\\ b=12 \qquad and \qquad 18+c=10\\ b=12 \qquad and \qquad c=-8\\\)

 

so

 

\(y= -18+3b+c\\ y= -18+3*12+-8\\ y=-18+36-8\\ y=10 \)

 

So the vertex is   (3,10)

 

Which is exactly the same answer has given you. He has done it a number of different ways but stlill all the answers are the same!!

 

Thanks EP :)

Melody  Feb 21, 2018

30 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.